Equity incentives and earnings management - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2005)
This paper examines the link between managers' equity incentives—arising from stock-based compensation and stock ownership—and earnings management. We hypothesize that managers with high equity incentives are more likely to sell shares in the future and this motivates these managers to engage in earnings management to increase the value of the shares to be sold. Using stock-based compensation and stock ownership data over the 1993–2000 time period, we document that managers with high equity incentives sell more shares in subsequent periods. As expected, we find that managers with high equity incentives are more likely to report earnings that meet or just beat analysts' forecasts. We also find that managers with consistently high equity incentives are less likely to report large positive earnings surprises. This finding is consistent with the wealth of thesemanagers being more sensitive to future stock performance, which leads to increased reserving of current earnings to avoid future earningsdisappointments. Collectively, our results indicate that equity incentives lead to incentives for earnings management.